Support Structures and Their Impacts on Employee Outcomes: A Longitudinal Field Study of an Enterprise System Implementation1 - Sykes, Tracy Ann (MIS Quarterly, 2015)
Despite the impressive progress in understanding the benefits and challenges related to enterprise system (ES) implementations—such as enterprise resource planning (ERP) systems—little is known about how the support structures traditionally used by organizations to help employees cope with a new ES affect employee outcomes related to the system and their jobs. Likewise, little is known about how existing peer advice ties in the business unit influence these outcomes after an ES implementation. Understanding employee outcomes is critical because of their ramifications for long-term ES success. This paper examines the impacts of four traditional support structures (namely, training, online support, help desk support, and change management support), and peer advice ties on four key employee outcomes (namely, system satisfaction, job stress, job satisfaction, and job performance). This paper also seeks to show that it is peer advice ties that best fill the complex informational needs of employees after an ES implementation by providing the right information at the right time and in the right context. The proposed model was tested in a field study conducted in one business unit of a large telecommunications company and gathered data from 120 supplier liaisons over the course of a year. Both traditional support structures and peer advice ties were found to influence the various outcomes, even after controlling for pre-implementation levels of the dependent variables. In all cases, peer advice ties was the strongest predictor, thus underscoring the importance of this critical internal resource.